Reducing relapse through maintenance steroid treatment can decrease the cancer risk in patients with IgG4‐sclerosing cholangitis: Based on a Japanese nationwide study. Issue 4 (10th January 2023) - Kubota, Kensuke; Kamisawa, Terumi; Nakazawa, Takahiro; Tanaka, Atsushi; Naitoh, Itaru; Kurita, Yusuke; Takikawa, Hajime; Unno, Michiaki; Kawa, Shigeyuki; Masamune, Atsushi; Nakamura, Seiji; Okazaki, Kazuichi; et al.
Abstract: Objective: IgG4‐related sclerosing cholangitis (IgG4‐SC) is recognized as a benign steroid‐responsive disease; however, little is known about the risk of development of cancer in patients with IgG4‐SC and about how to counter this risk. Design: We conducted a retrospective review of the data of 924 patients with IgG4‐SC selected from a Japanese nationwide survey. The incidence, type of malignancy, and risk of malignancy in these patients were examined. Then, the standardized incidence ratio (SIR) of cancer in patients with IgG4‐SC was calculated. Results: Relapse was recognized in 19.7% (182/924) of patients, and cancer development was noted in 15% (139/924) of patients. Multivariate analysis identified only relapse as an independent risk factor for the development of cancer. In most of these patients with pancreato‐biliary cancer, the cancer developed within 8 years after the diagnosis of IgG4‐SC. The SIR for cancer after the diagnosis of IgG4‐SC was 12.68 (95% confidence interval [CI] 6.89–8.79). The SIRs of cancers involving the biliary system and pancreas were 27.35 and 18.43, respectively. The cumulative survival rate was significantly better in the group that received maintenance steroid treatment (MST) than in the group that did not; thus, MST influenced the prognosis of these patients. Conclusion: Among the cancers, the risk of pancreatic and biliary cancers is the highest in these patients. Because of the elevated cancer risk, surveillance after the diagnosis and management to prevent relapse are important in patients with IgG4‐SC to reduce the risk of development of cancer.